Serological identification of listeria monocytogenes isolated from food using slide agglutination test - Rupel, Tatjana (Zdravstveno varstvo, 2003)
Listeria monocytogenes is subdivided into 13 serotypes on the basis of somatic(O) and flagellar (H) antigens. Because a vast majority of human disease are caused by only three serotypes (1/2a, 1/2b and 4b), serotyping is of limited value in epidemiologic investigations. Strains of Listeria monocytogenes isolated from food have been collected at the Department of Sanitary Microbiology since 1994. Pure cultures of Listeria recovered from foods were confirmed with the api-Listeria test (bioMerieux). Serological slide agglutination test was done on all Listeria monocytogenes isolates, using commercial antisera Bacto - Listeria O Antisera Types 1,4 and Poly (Difco). The 56 strains obtained were classified into 2 serovars. There were 46 strains of Listeria monocytogenes serotype 1, and six strains of serotype 4; the test for four strains was negative. The aim of subtyping Listeria monocytogenes isolates was to identify serotypes that had been most frequentlyisolated from food samples.
Keywords: infekcije; izolacija; listeria monocytogenes; živila